Innovative Technologies for Enhanced Physical and Mathematical Learning in Central Europe: Contemporary Issues and Trends of Fractal Structuring of Information - Mar’yan Mykhaylo; Nataliya Yurkovych; Vladimir Seben; Nikola Tesľuková (Journal of Vasyl Stefanyk Precarpathian National University)
The implementation of the functioning of fractals and fractality for open and holistic systems of physical and mathematical education is substantiated. It is shown that it is thanks to fractality that the synergy of the nature of the functioning of education, business, ecology, and human life as open systems is realized. In this article, the main emphasis is placed on considering the fractality of the functioning of physical and mathematical education in the countries of Central Europe on the example of cooperation between two universities – the University of Presov (Slovakia) and Uzhhorod National University (Ukraine). The relationship between fractality and information is analyzed. Iterations of the integrated fractal structure are presented using the example of studying physics sections, “Geometric optics” and “Wave optic” with information use of features geometric, algebraic, and stochastic fractals. It is shown that the principles of object-oriented programming, namely, encapsulation, inheritance, and polymorphism, are also characteristic of fractals. The application of the fractal approach to the structuring of information in physical and mathematical education is substantiated. It is shown that each iteration is characterized by synergy - the addition of a new iteration provides a high-quality and in-depth perception of new information. It manifests also the formation of an integrated fractal structure and corresponding iterations that reflect the integrity and spontaneity of the fractal perception of information. Based on the proposed approach to the use of interdisciplinary areas of knowledge and computer modeling, the fractal structure is formed at an intuitive level for students. The proposed approach provides the opportunity to most adequately implement the integration of education and information technologies to achieve the goals of holistic and continuous development adopted by the UN General Assembly.